Dampak lingkungan kerja, disiplin kerja dan kompensasi terhadap kinerja karyawan saat bekerja dari rumah - Uhai, Sabalius; Siskawati, Eka; Makkulawu Panyiwi Kessi, Andi; Yuniarti Utami, Eva; Liswandi, Liswandi (Nur Science Institute, 2024)
Remote work poses challenges for companies to ensure employees remain effective in their roles. This study aims to examine whether work environment, work discipline, and compensation individually or simultaneously influence employee performance during remote work. This is a quantitative study involving a sample of 55 employees currently working from home. Data were collected using a questionnaire with a Likert scale and subsequently analyzed. Instrument testing confirmed that all items were valid and reliable. The findings revealed that work environment, work discipline, and compensation positively and significantly influence employee performance both individually and simultaneously during remote work. This research provides several important implications that can assist companies in optimizing employee performance while working from home. Moreover, companies can enhance overall employee performance and achieve greater efficiency and productivity in remote work settings.